Parental responsibility for pediatric ventricular assist devices: Views of families on the acceptability of hospital discharge. (16th December 2019) - Crowe, Lisa; Simpson, Emma; Reinhardt, Zdenka; Rankin, Judith
Abstract: Background: Paracorporeal pediatric VAD therapy requires hospital residency due to device and patient factors. Discharge home is potentially possible with a mobile driving unit. This study aimed to investigate family views on hospital discharge of a child on VAD. Methods: Qualitative methodologies were adopted. We undertook 24 interviews of families who had a transplanted child previously on a VAD, and participant observations of two families who were current VAD patients residing in hospital. Results: Families experienced overwhelming emotions as they spent time adjusting to the diagnosis, the need for transplant, family separation, and financial concerns. Despite many parents being partially/fully trained on the VAD, the majority would be reluctant to be discharged, fearing emergencies, high burden of care needs, and social isolation. Three families with a child on a Berlin Heart expressed willingness to reside in the hospital accommodation at least part‐time, to facilitate private family time. One child on HeartWare was discharged home, with another going through the discharge process. Discharge was not acceptable to most families if this meant downgrading their child's transplant listing urgency status. Conclusion: Parents and children on VAD value independence and some private family time but not at the perceived expense of safety. Families preferred their child on VAD to remain resident in hospital even if mobility is improved with a mobile driving device. Parental education should acknowledge the high burden on families, risks of a remote setting and offer intermediate residency options. It cannot be assumed families want hospital discharge.